Daurisoline Modulates the TBK1-Dependent Type I Interferon Pathway to Boost Anti-tumor Immunity via Targeting of LRP1 - Borui Tang; Yuting Wang; Liping Li; Cuicui Sun; Jingwen Dong; Ruoqi Li; Jianfeng Wang; Yu Long; Mingxiao Yin; Fei Xie; Dian Xiao; Xinbo Zhou; et al. (Research)
A promising therapeutic approach in oncology involves immune checkpoint blockade (ICB), which stimulates anti-tumor immune responses. Nevertheless, the effectiveness of this treatment in clinical settings remains limited, underscoring the need for complementary strategies. Recent studies highlight the potential of type I interferon (IFN-I) inducers to reprogram the tumor microenvironment and enhance ICB outcomes. Herein, through high-content screening of a natural compound library, we identified daurisoline (DS), a bioactive alkaloid extracted from the Chinese herbal medicine Rhizoma Menispermi, as a potent inducer of IFN-I signaling. Our findings indicated that DS up-regulates interferon responses and pro-inflammatory cytokine expression in a TANK-binding kinase 1 (TBK1)-dependent manner. In vivo, DS exhibited marked tumor growth inhibition by activating dendritic cells, macrophages, and CD8+ T cells, thereby enhancing anti-tumor immunity. Utilizing the LiP-SMap approach, we identified low-density lipoprotein receptor-related protein 1 (LRP1) as the direct target of DS. Mechanistically, the binding of DS to LRP1 substantially disrupted lysosomal function, which subsequently triggered 5′-azacytidine-induced protein 2-mediated TBK1 activation and IFN-I production. Furthermore, DS demonstrated synergistic effects with anti-programmed death 1 therapy and a stimulator of interferon genes agonist by remodeling the immunosuppressive microenvironment. Collectively, our findings establish LRP1 as a novel therapeutic target for cancer immunotherapy and highlight DS-driven immune reprogramming as a translatable strategy to potentiate ICB efficacy.